Resistance webs: survival and resistance of native american peoples in 'There there' by Tommy Orange - Perotes, Wevelly Thaissa ribeiro; Rocha, Ana Lilia Carvalho; de Alencar, Larissa Fontinelle (Revista X, 2024)
This paper examines how the metaphor of the spider web in There There (2016) by Native American writer Tommy Orange is utilized to convey a message of resistance and survival of Native American peoples. The analysis explores the cultural symbolism of the spider web and its relationship to the three characters in the narrative, drawing on theoretical approaches from authors such as Hertha D. Wong and Sergiusz Michalski. Additionally, Achille Mbembe's concept of necropolitics is incorporated into the analysis, linking it to the historical policies of genocide and social exclusion applied to Native American peoples. By studying authors such as Vine Deloria Jr., Ward Churchill, and Roxanne Dunbar-Ortiz, one can understand how the cultural and territorial genocide policies applied to Native American peoples in the United States were used to justify the exploitation of their natural resources and the usurpation of their lands. Thus, this analysis offers a critical and broad perspective on the struggle of Native American peoples for their survival and resistance and seeks to demonstrate how necropolitics is present in the narrative and how it affects the mentioned characterance